Prospects for the development of science and higher education in the Republic of Kazakhstan: Gender patterns - Bisenbaev, Adilbek K.; Bizhkenova, Aigul E.; Aktanova, Aiman S.; Fakhrutdinova, Anastasia V. (Вестник Томского государственного университета)
Gender equality is a fundamental catalyst for economic development and societal prosperity. This study is undertaken to explore gender patterns within the academic community of Kazakhstan. The research employs statistical data to quantitatively assess the representation of women and men, analyzing age-related characteristics of individuals who have obtained a PhD in Kazakhstan with the aim of identifying gender differences within the academic community. The results indicate that gender equality has been achieved at institutional and organizational levels, yet pervasive "social barriers" still hinder the full recognition of women's accomplishments. A notable phenomenon observed in the scientific system of Kazakhstan is the trend of feminization, which emerged in 2012 when the number of female researchers (9,316) surpassed that of their male counterparts (7,776). However, in this landscape characterized by gender and social inequality, a parallel effect of gender inversion emerged. Women scientists face specific challenges in transitioning from a PhD to the subsequent Doctor of Science (DrS) degree, as recognized in Kazakhstan. While the number of female researchers with a PhD degree is nearly twice that of male researchers, the number of female researchers with a DrS degree significantly lags behind their male colleagues. This gender inversion effect is explored through the prism of social factors, shedding light on a complex issue that requires further investigation and intervention to promote true gender equality in science and academia. As a recommendation to mitigate the effects of gender inversion and "social barriers" in the field of science, the authors propose a restructuring of the scientific metric system. This involves reducing the dominance of quantitative (numeric) and temporal (time-based) assessments while increasing the importance of qualitative (humanitarian) assessments of potential, productivity, and research efficiency. Additionally, the authors suggest the development, adoption, and implementation of specialized programs aimed at improving the social life of researchers to achieve family ergonomics. Furthermore, qualifications should be taken into account, with grants, memberships, hierarchical positions, and recognition in the scientific system considering only a PhD degree (or candidate of sciences) within the Bologna Process, diminishing the value of academic degrees such as "Doctor of Sciences" and "Doctor of Proficiency". Lastly, quantitative stimulation of diverse scientific groups is recommended through appropriate regulatory acts and supervisory functions.